Degraded power MOSFET effects on Class-A power amplifier: Modelling studies considering feedback. (July 2021) - Meydanci, Mehmet Akif; Özçelep, Yasin
Abstract: The purpose of the study is proposing a gate oxide degraded MOSFET model that represents the degraded MOSFET effects on Class-A power amplifier parameters. The model includes electrical stress induced threshold voltage and transconductance parameter instabilities of transistor. The change in threshold voltage is between 3.2 V and -1 V; the change in transconductance parameter is between 0.4A/V 2 and 0.004A/V 2 . The circuit model is formed by using a voltage source at the gate terminal and a resistor at the source terminal of transistor. Simulations with the proposed model are performed and simulation results are compared experimental DC and AC measurements of Class-A amplifier with and without feedback resistor during stress. To improve the model, we also proposed a tuning circuit. Its seen that, the proposed model in the study is successful to simulate the stress induced change in gain, efficiency of Class-A power amplifier. Highlights: We proposed gate oxide degraded MOSFET model representing degraded MOSFET effects on Class-A power amplifier parameters. The model includes threshold voltage and transconductance instabilities of transistor. Stress induced change in gain and efficiency of Class-A power amplifier are successfully simulated using proposed model.